Time to treatment initiation and retrospective analysis of antiretroviral therapy outcomes among HIV-positive methadone maintenance therapy clients in Primary Health-care Centers, Kuantan, Pahang - Ramlan, Aida Roziana; Nazar, Nor Ilyani; Tumian, Afidalina; Ab Rahman, Norny Syafinaz; Mohamad, Dzawani; Abdul Talib, Mat Sharil; M. Zakaria, Khairul Faizan; Izuddin, Muhammad Azzim; Zainal Abidin, Nadia Akmal; T. Syed Manso, Syarifah Syafiqah; Wan Hassan, Wan Nur Khairiyah (Wolters-Kluwer, 2020)
Introduction: Methadone maintenance therapy (MMT) program helped to improve access to antiretroviral therapy (ART) among people who inject drugs (PWID) with human immunodeficiency virus (HIV). However, the time to treatment initiation (TTI) and outcomes of ART intervention in this population have scarcely been analyzed. Objectives: The aim of this study was to analyze the TTI and outcomes of ART among MMT clients in primary health-care centers in Kuantan, Pahang. Materials and Methods: This was a retrospective evaluation of MMT clients from 2006 to 2019. The TTI was calculated from the day of MMT enrolment to ART initiation. The trends of CD4 counts and viral loads were descriptively evaluated. Cox proportional hazard model was used to analyze the survival and treatment retention rate. Results: A total of 67 MMT clients from six primary health-care centers were HIV-positive, of which 37 clients were started on ART. The mean TTI of ART was 27 months. The clients who were given ART had a mean CD4 count of 119 cells/mm3 at baseline and increased to 219 cells/mm3 after 6 months of ART. Only two patients (5.4%) in the ART subgroup had an unsuppressed viral load. The initiation of ART had reduced the risk of death by 72.8% (hazard ratio = 0.27, P = 0.024), and they are 13.1 times more likely to remain in treatment (P < 0.01). Conclusion: The TTI of ART was delayed in this population. MMT clients who were given ART have better CD4 and viral load outcomes, helped reduced death risk and showed higher retention rates in MMT program.